The role of the cartilaginous to osseous acetabular angle ratio in children with developmental dysplasia of the hip - Jiaqi Wang; Tianyou Li; Yangyang Yao; Chaoqun Lu; Yanzhou Wang (Frontiers Media S.A., 2024)
PurposeThis study aims to demonstrate the use of the cartilaginous to osseous acetabular angle ratio (AAR) in surgical decision-making for hip dysplasia.MethodsData were collected from patients who underwent an MRI of the hip after conservative treatment for developmental dysplasia of the hip between August 2019 and 2022. The data included demographic information as well as an anteroposterior pelvic radiograph. The osseous acetabular index (OAI) was measured using x-ray, while the cartilaginous acetabular index (CAI) and the cartilaginous acetabulum head index (CAHI) were measured using MRI. The square of the CAI to OAI, AAR, was calculated. The patients in the residual hip dysplasia (RHD) group were categorized as having an OAI above 20°. During the postoperative follow-up, we evaluated the patients in this group who underwent Bernese triple pelvic osteotomy. Data on surgical patients with an observation period that exceeded 1 year were collected and analyzed. The distribution of the AAR among the different groups was analyzed. A receiver operating characteristic (ROC) predictive model was constructed using the AAR of the patients in the normal and surgical groups to evaluate the need for surgery.ResultsIt was found that there was a significant difference in the OAI, CAI, CAHI, and AAR between the RHD group (OAI 26.15 ± 3.90°, CAI 11.71 ± 4.70°, CAHI 79.75 ± 6.27%, and AAR 5.88 ± 4.24) and the control group patients (OAI 16.77 ± 5.39°, CAI 6.16 ± 3.13°, CAHI 85.05 ± 4.91%, and AAR 2.71 ± 2.08) (p < 0.001). A total of 93.5% of the control group patients had an AAR ≤5, while only 6.5% had an AAR >5. The results of postoperative imaging follow-up were "excellent" in 52 patients and "good" in 3, while the functional follow-up results were excellent in 53 and good in 2. In 15 patients, the observation period exceeded 1 year. The mean observation period was 633.1 ± 259.6 days and the preoperative CAHI was 71.7 ± 4.8%. Of the patients with an AAR >5, a substantial 94.8% (55/58) of them were reported to have undergone surgery, while all patients with an AAR less than or equal to 5 did not undergo surgery (91/91). Based on the ROC, a cutoff value of 5.09 was identified for the need for surgery in children with RHD.ConclusionsA surgical decision for residual hip dysplasia can be based on the AAR. An AAR >5 may be a potential indicator for surgical intervention in patients with RHD.